MUTU PATI SAGU YANG DIHASILKAN MELALUI PROSES PERENDAMAN DAN PENGADUKAN EMPULUR SAGU - Surianto '; Akhyar Ali; Noviar Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purposeof this studywas to determinehowlongthe effect ofsoaking andstirringthesagopithof sagostarchproductionquality. This study was conductedexperimentallyusing aComplete Random Design(CRD) withtwofactorials. The first factoris thesoaking time that consists ofthree levelsandthe second factoris the length ofthe stirring that consists oftwo levels. Soakingis donewiththe composition of15litersof water/kg ofsagopith. Stirringis donemechanicallywith a speed of620rpm. The results showedthat there is no significant effecton the quality ofsagostarchproduced in theinteractionbetween thelongsoaking timeandstirringno. Based on thetreatment factor, longagitationalso did not give significant effectonimproving the quality ofsagostarch and soaking timetreatments gave significant effecton the quality ofsagostarch.  Generally, the combinationtreatment of R3A2(Soaking for 15hoursandstirring for2minutes) is thebesttreatment, the yield ofsagostarchproducedby50.57%, ash content0.46%, the starch content of54.84%,  0.41% of fiber content, texturesmooth, grayish-whitecolorand littletasteof sago. Keywords: SagoStarch, immersionandstirring